Formasi Jabatan Notaris dan Penentuan Kategori Daerah Pasca Perubahan - Neilul Muna (Officium Notarium, 2022)
This research is motivated by the existence of legal dynamics in regulating the formation of notary positions and the determination of regional categories after the changes to the Notary Public Law (UUJN). The issues raised in this study include the background of the reformulation of the formation of notary positions and the determination of regional categories after the amendment of the UUJN and how the flow of arrangements for the formation of notary positions and the determination of regional categories after the amendment of UUJN. This study uses a normative juridical method with a statutory and analytical approach. The results of the study concluded: First, after the amendment of the UUJN there were 4 (four) Ministerial Regulations (Perkemenkumham) governing the formation of notary positions and the categories for determining areas including: Permenkumham No.36/2015 jo. Permenkumham No.26/2014, Permenkumhan No.27/2016, and what is currently in force is Permenkumham No.19/2021. The reason behind the formation setup of notary positions and categories for determining regions specifically requires rearrangement of previous regulations by taking into account population growth, economic growth and regional expansion. Second, the trajectory of setting up the formation of notary positions and determining regional categories begins with limiting the number of notaries to changing regional categories. However, at this time, Permenkumham No.19/2021 provides clarity regarding the procedures for filling in the notary position formation, collecting notary data and simplification of regional categories and specifically stipulating procedures for submitting applications for moving regions.Key Word: Legal Dynamics, Arrangement, Notary Formation. AbstrakPenelitian ini dilatarbelakangi adanya dinamika hukum pengaturan formasi jabatan notaris dan penentuan kategori daerah pasca perubahan Undang-Undang Jabatan Notaris (UUJN). Permasalahan yang diangkat dalam penelitian ini mencakup bagaimana latar belakang direformulasinya formasi jabatan notaris dan penentuan kategori daerah pasca perubahan UUJN dan bagaimana alur pengaturan formasi jabatan notaris dan penentuan kategori daerah pasca perubahan UUJN. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan peraturan perundang-undangan dan pendekatan analisis. Hasil penelitian menyimpulkan: Pertama, pasca perubahan UUJN terdapat 4 (empat) Peraturan Menteri yang mengatur formasi jabatan notaris dan kategori penentuan daerah mencakup: Permenkumham No.36/2015 jo. Permenkumham No.26/2014, Permenkumhan No.27/2016, dan yang saat ini berlaku adalah Permenkumham No.19/2021. Latar belakang pengaturan formasi jabatan notaris dan kategori penentuan daerah secara khusus diperlukan penataan kembali terhadap regulasi terdahulu dengan memperhatikan pertambahan jumlah penduduk, pertumbuhan ekonomi dan pemekaran daerah. Kedua, trajektori pengaturan formasi jabatan notaris dan kategori penentuan daerah dimulai dengan melakukan pembatasan jumlah notaris hingga mengubah kategori daerah. Namun saat ini, Permenkumham No.19/2021 memberi kejelasan terkait tata cara pengisian formasi jabatan notaris, melakukan pendataan notaris dan simplifikasi kategori daerah serta mengatur secara spesifik tata cara pengajuan permohonan pindah wilayah.Kata-kata Kunci: Dinamika Hukum, Penataan, Formasi Jabatan Notaris.